Evaluation of Agricultural Faculty Students’ Perspectives on Expert Hands in Rural Development Project; The Case of Yozgat Bozok University - TENGİZ, Zehra Meliha and AYYILDIZ, Merve and ÇİÇEK, Adnan (ISPEC Journal of Agricultural Sciences, 2023)
In this study, it is aimed to determine the knowledge of the young people receiving agricultural education about the “Expert Hands İn Rural Development Project”, their thoughts on benefiting and the factors affecting it, and also to evaluate their attitudes towards agriculture. Fort his purpose, data obtained from Yozgat Bozok University Faculty of Agriculture students in March-April 2022. The results showed that many students considered working in agriculture after graduation, and it was found that the presence of the family in agricultural production determined the largest role in this decision. However, the proportion of young people who want to benefit from the project is low. The fact that the project has not become widespread yet can be explained by the inadequacy of the grant amount and the search for too many prerequisites. In order for the project to achieve the desired success, it is considered important to determine different and sufficient grant amounts, taking into account the fields of activity. Additionally, for grant programs successful, policies aiming at raising living conditions in rural regions must also be developed.